Soy Protein Isolate/Poly (Vinyl Alcohol) Films with IPN Structure by Crosslinkage of Ferulic Acid - Su, Jun-Feng; Wang, Ying-Yuan; Han, Shan; Zhang, Xiao-Long (Journal of Research Updates in Polymer Science, 2016)
Blend films from nature soy protein isolates (SPI) and synthetical poly (vinyl alcohol) (PVA) were successfully fabricated by crosslinkage of ferulic acid (FA) based on a solution-casting method. Structure analysis results indicated that FA had chemical reactions with both SPI and PVA, a three-dimensional interpenetrated polymer networks (IPN) had formed between SPI and PVA. The miscibility of SPI/PVA blends had improved by crosslinkage of FA. Moreover, the transparency of films had enhanced with the increasing of FA contents, which proved the INP structure of SPI/PVA blends could be adjusted by cross-linking degree. This method supplies a highlight potential usage of SPI as environmental-friendly packaging films.